2007
DOI: 10.1128/iai.01442-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Monocyte Chemotactic Protein 1 in Colonic Epithelial Cells by Entamoeba histolytica Is Mediated via the Phosphatidylinositol 3-Kinase/p65 Pathway

Abstract: The role intestinal epithelial cells play in the pathogenesis of amebic colitis is poorly understood. Herein, we demonstrate that secreted and soluble ameba (Entamoeba histolytica) proteins (SAP) induce expression of the chemoattractant monocyte chemotactic protein (MCP) in the colonic epithelial cell lines Caco-2, T84, and LS174T. MCP-1 mRNA induction was both dose and time dependent, with peak induction occurring at 8 h and with 100 g/ml of SAP. Significant increase in MCP-1 protein expression was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…It has been found that both the C-X-C and C-C members of the chemokine family of proteins, as well as the proinflammatory cytokines IL-1␤, IL-6, and tumor necrosis factor alpha and the cell growth factor GM-CSF, are released by epithelial cells after bacterium-enterocyte interactions (27). Recently, we showed that in colonic epithelial cells, monocyte chemoattractant protein 1 is secreted in response to soluble ameba components via the phosphatidylinositol 3-kinase/P65 pathway (16). The release of this cytokine in vivo by the epithelium would be an effective means of initiating a mucosal inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that both the C-X-C and C-C members of the chemokine family of proteins, as well as the proinflammatory cytokines IL-1␤, IL-6, and tumor necrosis factor alpha and the cell growth factor GM-CSF, are released by epithelial cells after bacterium-enterocyte interactions (27). Recently, we showed that in colonic epithelial cells, monocyte chemoattractant protein 1 is secreted in response to soluble ameba components via the phosphatidylinositol 3-kinase/P65 pathway (16). The release of this cytokine in vivo by the epithelium would be an effective means of initiating a mucosal inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant change in total p38 protein levels in VacAtreated Jurkat cells. Recent evidence suggests that the PI3K/ Akt pathway also modulates the NF-B signaling pathway (27). Therefore, Akt activation was checked with antibodies that specifically recognize phosphorylated Akt.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The trophozoites of E. histolytica are capable of inhibiting the action of complement proteins Que et al, 2003;Que & Reed, 2000). c. Inflammation is induced by cytokines of colonic epithelial cells (Eckmann et al, 1995;Kammanadiminti et al, 2007;Seydel et al, 1997;Yu & Chadee, 1997). d. A type 2 (Th2) immune response predominates during amebic colitis.…”
Section: Fig 1 Amebic Nodular Necrotic Ulcers (Arrows) and Amebic Imentioning
confidence: 99%
“…Various researchers have queried about the role played by the immune response in this pathology (Ventura-Juárez et al, 2002. For instance, perhaps the inflammatory response has the objective of eliminating the amebas, only to end up participating in the pathogenesis (Kammanadiminti et al, 2007;Seydel et al, 1998).…”
Section: Fig 1 Amebic Nodular Necrotic Ulcers (Arrows) and Amebic Imentioning
confidence: 99%